Systematic review of literature, RED and art teaching - Isana, Lilian; Antunes, Ivanir; Fiuza, Patrícia Jantsch; Biz, Rita de Cassia Martins (Seven Editora, 2023)
This article refers to the systematic review of literature presented in the master’s dissertation entitled "Digital Educational Resources and the teaching of Art in Municipal and State Basic Education in the region of the Association of Municipalities of the Extreme South of Santa Catarina AMESC", with the objective of analyzing the educational practices with the use of Digital Educational Resources in the teaching of Arts in Municipal and State Basic Education in the region of the Association of Municipalities of the Extreme South Catarinense – AMESC. Initially, the search resulted in 1,111 studies in the ten-year period, the search was refined for the last five years, resulting in 390 studies, and after a thorough review, based on the selection and exclusion criteria, resulted in the identification of (22) studies that relate the variables defined in the Systematic Literature Review protocol. DOI:https://doi.org/10.56238/sevened2023.004-051